2022
DOI: 10.1155/2022/9548316
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Analysis Reveals Alterations in Cochlear Metabolic Profiling in Mice with Noise-Induced Hearing Loss

Abstract: Noise-induced hearing loss (NIHL) has always been an important occupational hazard, but the exact etiopathogenesis underlying NIHL remains unclear. Herein, we aimed to find metabolic biomarkers involved in the development of NIHL based on a mouse model using a gas chromatography coupled with mass spectrometry (GC-MS) metabolomics technique. We showed that the auditory brainstem response (ABR) thresholds at the frequencies of 4, 8, 12, 16, 24, and 32 kHz were all significantly elevated in the noise-exposed mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 43 publications
(46 reference statements)
0
11
0
Order By: Relevance
“…The data were then entered into the MS-DIAL software for preprocessing. Metabolites were characterized using LUG database (Lumingbio Untargeted database of GC-MS) ( He et al, 2022 ; Miao et al, 2022 ), and a data matrix was derived. The three-dimensional matrix includes: sample information, the peak name for each substance, retention time, retention index, mass-to-charge ratio, and signal intensity.…”
Section: Methodsmentioning
confidence: 99%
“…The data were then entered into the MS-DIAL software for preprocessing. Metabolites were characterized using LUG database (Lumingbio Untargeted database of GC-MS) ( He et al, 2022 ; Miao et al, 2022 ), and a data matrix was derived. The three-dimensional matrix includes: sample information, the peak name for each substance, retention time, retention index, mass-to-charge ratio, and signal intensity.…”
Section: Methodsmentioning
confidence: 99%
“…Metabolomics, reflecting both genetic traits and environmental influences, plays a crucial role in understanding various forms of hearing impairment [97]. Recent studies have reported consistent data on the predictive role of serum metabolic profiles in sudden hearing loss [98], noise-induced hearing loss [99], and the identification of markers for ototoxicity [97,100]. Metabolomic investigations may pave the way for improved diagnostic strategies, personalized interventions, and targeted treatments, ultimately enhancing the clinical management of individuals affected by different causes of hearing loss [101,102].…”
Section: Metabolomicsmentioning
confidence: 99%
“…Table 2 shows the key features of the included studies on animal models. Of them, 3 were performed on guinea pigs [45][46][47], 1 on rats [48], 2 on mice [49,50] and 1 on sheep [51]. Metabolomic profiling was conducted using LC-MS techniques in four studies [45,47,49,50], while in the others GC-MS was applied [46,48,51].…”
Section: Metabolomics Investigations On Animal Models Of Hearing Lossmentioning
confidence: 99%